Inside Cover: Structural Evolution of Water on ZnO(101‾ 0): From Isolated Monomers via Anisotropic H‐Bonded 2D and 3D Structures to Isotropic Multilayers (Angew. Chem. Int. Ed. 49/2019). Issue 49 (8th November 2019) - Yu, Xiaojuan; Schwarz, Paul; Nefedov, Alexei; Meyer, Bernd; Wang, Yuemin; Wöll, Christof
Abstract : An atomic‐level picture of the structural evolution of water on the anisotropic ZnO(10 1 ‾ 0) surface was investigated by Y. Wang, C. Wöll et al. in their Research Article on page 17751 ff. by combining experiment and theory. IR spectroscopic evidence of isolated, intact D2 O monomers is provided. The hydration proceeds further through an autocatalytic dissociation of dimers, followed by the formation of a mixed 2D D2 O/OD adlayer and various complex H‐bonded 3D structures.